EKSPRESI MENULIS DAN MENGGAMBAR SEBAGAI MEDIA TERAPI - Dian Sari Utami; Amitya Kumara (Faculty of Psychology, Universitas Gadjah Mada, 2003)
Children are very vulnerable with their body, especially when they are ill. This condition is so uncomfortable for children to get ill, moreover when they have to hospitalized. Children which in hospitalized condition usually have chronic illness and should be hospitalized for long time. This condition would affects not only their body, but their mind and emotion. Hospitalized would make children getting stress and distress and need to cope. One way to cope is by managing their emotion through writing and drawing as a method to express their emotion. This study used the book as a media to express their emotion called “Pelangi Hatiku”. The qualitative method using in this study is case study. The participants who involved in this case study are 3 children of 8-12 year-old from 2 general hospital in Yogyakarta. Children were interviewed and observed regarding their: (a) understanding of positive and negative emotions, and (b) ways of regulating emotion before and after they using “Pelangi Hatiku” for several times. It was found that the children have understanding of their negative and positive emotions, and able to express them to others. They have four ways to manage their emotions that are necessary for healthy adjustment. Therefore, the book of “Pelangi Hatiku” can be used as a therapy media for hospitalized children. Keywords: hospitalized children, buku “Pelangi Hatiku”, media therapy.